(untitled) (Tanzania Medical Journal, 2015)
Background: Drug resistant Tuberculosis is well documented worldwide and is associated with increasing morbidity and mortality complicating Tuberculosis control with increasing costs of managing the disease. Broad Objective: To describe clinical and laboratory characteristics of multi-drug resistant Tuberculosis (MDR-TB) patients on second line anti-TB drugs at Kibong?oto hospital in Tanzania.Methodology: A retrospective cohort study for MDR-TB patients in 56 patients on second line anti-TB treatment at Kibong?oto hospital and cross sectional study in 40 close contacts for MDR-TB residing in Dar-es-Salaam. Information of patients was abstracted from the MDR-TB register book and clinical file clinical notes containing demographics, clinical and radiological information at baseline and after treatment initiation, first line anti-TB drugs use, bacteriology results at baseline and after treatment initiation that were available at Kibong?oto hospital. A questionnaire was used to record clinical and demographic characteristics of MDR-TB close contacts. Sputum smear collection and chest radiographs were performed on MDR-TB close contacts with respiratory symptoms suggestive of Tuberculosis.Results: Fifty two (92.9%) patients had confirmed MDR-TB and four patients were started on empirically on second line anti-TB drugs following clinical deterioration despite negative cultures. Nine (16.1%) patients were HIV infected. Thirty two (57.2%) patients improved clinically with negative sputum smears and cultures six months after treatment initiation and were discharged home to their nearest centers to continue with intensive phase of treatment. Six (10.7%) patients died, 3 (5.4%) patients defaulted and 15 (26.8%) patients were still on initiation phase of treatment at the hospital. Twenty four (42.9%) patients experienced at least one drug adverse event while on treatment. None of MDR-TB close contact had active Tuberculosis.Conclusion and recommendations: This study shows that MDR-TB patients had a good treatment response following use of second line anti- TB drugs. This data suggests the need of Rapid diagnostic methods such as PCR for early diagnosis and therefore early treatment before clinical worsening or death.